Monte Carlo method at the 24 game and its application for mathematics education - Fitrianawati, Meita; Aliansyah, Zulhaj; Peni, Nur Robiah Nofikusumawati; Farid, Imam Wahyudi; Hakim, Lukman (Journal of Honai Math, 2022)
Students often find mathematics a challenging subject and turn it into a scourge for them. Game-based learning, such as â€œ24-card gameâ€, help engage students in a self-paced and fun learning process and thus may overcome studentsâ€™ math anxiety and promote mental math skills. This research aims to examine how the 24-card game works using the Monte Carlo method and the possibility to overcome students' mathematics anxiety. The meta-analysis method was used to explain Monte Carloâ€™s simulation to solve the solution for all possible combinations of cards in the game and respectively assign difficulty levels. The student's proficiency level was evaluated based on the divergence value in the number of guesses required to solve the dealt combination at 87% to show full proficiency. The evaluation could also show the math difficulty of advanced operations, such as fractions and grouping games. This game is more efficient in developing students' mental math skills compared to a conventional and rigidly structured classroom lecture.